Public-private partnerships in U.S. rural water infrastructure: challenges, opportunities, and needs - Sowby, Robert B.; Farnsworth, Clifton B.; South, Andrew J.; George, Grant A. (Frontiers in Water, 2025)
Most water and wastewater systems serve small, rural communities that often lack the scale, funding, and staffing to maintain their critical infrastructure. Public-private partnerships (PPPs or P3s) may be a solution. In this Perspective we diagnose the problems of rural water services and map the strengths of P3s to solve them. We discuss the challenges of adapting P3s to rural water infrastructure and suggest the most beneficial opportunities for doing so—namely, water utilities’ new assets, revenue/capital, and regional collaboration. The work offers insights into how rural water and wastewater systems might pursue P3s to sustainably manage their infrastructure needs.